2016
DOI: 10.18632/oncotarget.9882
|View full text |Cite
|
Sign up to set email alerts
|

Direct cell fate conversion of human somatic stem cells into cone and rod photoreceptor-like cells by inhibition of microRNA-203

Abstract: Stem cell-based photoreceptor differentiation strategies have been the recent focus of therapies for retinal degenerative diseases. Previous studies utilized embryonic stem (ES) cells and neural retina differentiation cocktails, including DKK1 and Noggin. Here, we show a novel microRNA-mediated strategy of retina differentiation from somatic stem cells, which are potential allogeneic cell sources. Human amniotic epithelial stem cells (AESCs) and umbilical cord blood-derived mesenchymal stem cells (UCB-MSCs) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…There have been also some reports about differentiation of bone marrow mesenchymal stem cells (BMSCs) into photoreceptors through inducing MSCs cultured with photoreceptors and conditioned medium in rat models [1, 10]. MiRNA-based differentiation is similarly known as a promising alternative technique that does not involve integration into the genome [11]. MiRNAs can also repress mRNA translation or lead to target mRNA degradation via complementarity binding to the 3′-UTR of target mRNAs [12].…”
Section: Introductionmentioning
confidence: 99%
“…There have been also some reports about differentiation of bone marrow mesenchymal stem cells (BMSCs) into photoreceptors through inducing MSCs cultured with photoreceptors and conditioned medium in rat models [1, 10]. MiRNA-based differentiation is similarly known as a promising alternative technique that does not involve integration into the genome [11]. MiRNAs can also repress mRNA translation or lead to target mRNA degradation via complementarity binding to the 3′-UTR of target mRNAs [12].…”
Section: Introductionmentioning
confidence: 99%
“…In ocular diseases, miR-203-3p was reported to serve as a novel regulator of zebrafish retina regeneration by repressing pax6b, which is necessary for progenitor cell expansion (57). Additionally, miR-203-3p is thought to be involved in the retinal differentiation of amniotic epithelial stem cells and umbilical cord blood-derived mesenchymal stem cells, possibly by targeting multiple retina development-relevant genes, such as dickkopf WNT signaling pathway inhibitor 1, cone-rod homeobox, RAR-related orphan receptor beta, neurogenic differentiation 1, neural retina leucine zipper and thyroid hormone receptor beta (58). The results of the present study suggest that the upregulated expression of angiogenesis-associated mRNAs, such as Hmox1 (59), Fn1 (60), Flna (61), Nrp1 (62), Kdr (63), Cav1 (64), Ptprb (65), Srpk2 (66), Hif1a (67), Efnb2 (68) and Mapk14 (69), which were predicted to be targets of miR-203-3p, may be regulated by circ_0005477, circ_0013414, circ_0012698 and circ_0000668 in ROP retinas.…”
Section: Discussionmentioning
confidence: 99%
“…(3) MSCs for retinal diseases The controlled expression of some internal and/or external components regulates the regeneration of mammalian cells at certain developmental stages (Jopling et al, 2011). In contrast to this theory, numerous studies have reported the possibility of MSC regeneration into endoderm and ectoderm lineage in in vitro and in vivo models (Choi et al, 2016). This phenomenon of pedigree transformation is termed as dedifferentiation or transdifferentiation (Guan et al, 2013).…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%